Diversidad e índice de valor de importancia del bosque varillal alto húmedo en las parcelas 3 y 4 del arboretum el “Huayo”, Puerto Almendra, Loreto, Perú 2021 - Pinedo Sotelo, Vilma Victoria Jazmin (2025)
The study was carried out in plots 3 and 4 of the high humid varillal forest of the arboretum “El Huayo”, belonging to the Forestry Research and Teaching Center of Puerto Almendra, attached to the Faculty of Forestry Sciences of the UNAP, in Iquitos, Peru. In order to evaluate the diversity and calculate the importance value index (IVI), a floristic inventory was carried out in areas of 1 ha with trees of DBH ≥ 10 cm, using subplots of 20 m x 20 m. In plot 3, Simpson's dominance index was 0.018, indicating high diversity and low dominance, with Eschweilera grandiflora as the predominant species (18 individuals). In plot 4, this index was 0,01731, confirming similar characteristics, with Eschweilera grandiflora again standing out (17 individuals). The Shannon-Wiener index was 4,51698 in plot 3 and 4,44691 in plot 4, reflecting remarkable biological diversity in both plots. Eschweilera grandiflora, Alchornea triplinervia and Eschweilera coriacea were the most outstanding species in plot 3, while Eschweilera grandiflora, Alchornea triplinervia and Helicostylis tomentosa were the most important in plot 4. In terms of IVI, the top 40 species in plot 3 accumulated a total of 151.53%, with Eschweilera grandiflora as the most relevant (IVI of 16,57%). In plot 4, the total IVI was 151,80%, with Tapirira retusa as the most important species (IVI of 13,88%). The results support the hypothesis, showing differences in diversity and IVI between the evaluated plots, reflecting the influence of specific ecological factors that highlight the heterogeneity of these tropical ecosystems.